Stress-inducible protein 1: a bioinformatic analysis of the human, mouse and yeast STI1 gene structure - Aken, Bronwen Louise (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2005)
Stress-inducible protein 1 (Sti1) is a 60 kDa eukaryotic protein that is important under stress and non-stress conditions. Human Sti1 is also known as the Hsp70/Hsp90 organising protein (Hop) that coordinates the functional cooperation of heat shock protein 70 (Hsp70) and heat shock protein 90 (Hsp90) during the folding of various transcription factors and kinases, including certain oncogenic proteins and prion proteins. Limited studies have been conducted on the STI1 gene structure. Thus, the aim of this study was to develop a comprehensive description of human STI1 (hSTI1), mouse STI1 (mSTI1), and yeast STI1 (ySTI1) genes, using a bioinformatic approach. Genes encoded near the STI1 loci were identified for the three organisms using National Centre for Biotechnology Information (NCBI) MapViewer and the Saccharomyces Genome Database. Exon/intron boundaries were predicted using Hidden Markov model gene prediction software (HMMGene) and Genscan, and by alignment of the mRNA sequence with the genomic DNA sequence. Transcription factor binding sites (TFBS) were predicted by scanning the region 1000 base pairs (bp) upstream of the STI1 orthologues' transcription start site (TSS) with Alibaba, Transcription element search software (TESS) and Transcription factor search (TFSearch). The promoter region was defined by comparing the number, type and position of TFBS across the orthologous STI1 genes. Additional putative TFBS were identified for ySTI1 by searching with software that aligns nucleic acid conserved elements (AlignACE) for over-represented motifs in the region upstream of the TSS of genes thought to be co-regulated with ySTI1. This study showed that hSTI1 and mSTI1 occur in a region of synteny with a number of genes of related function. Both hSTI1 and mSTI1 comprised 14 putative exons, while ySTI1 was encoded on a single exon. Human and mouse STI1 shared a perfectly conserved 55 bp region spanning their predicted TSS, although their TATA boxes were not conserved. A putative CpG island was identified in the region from -500 to +100 bp relative to the hSTI1 and mSTI1 TSS. This region overlapped with a region of high TFBS density, suggesting that the core promoter region was located in the region approximately 100 to 200 bp upstream of the TSS. Several conserved clusters of TFBS were also identified upstream of this promoter region, including binding sites for stimulatory protein 1 (Sp1), heat shock factor (HSF), nuclear factor kappa B (NF-kappaB), and the cAMP/enhancer binding protein (C/EBP). Microarray data suggested that ySTI1 was co-regulated with several heat shock proteins and substrates of the Hsp70/Hsp90 heterocomplex, and several putative regulatory elements were identified in the upstream region of these co-regulated genes, including a motif for HSF binding. The results of this research suggest several avenues of future experimental work, including the confirmation of the proposed core promoter, upstream regulatory elements, and CpG island, and the investigation into the co-regulation of mammalian STI1 with its surrounding genes. These results could also be used to inform STI1 gene knockout experiments in mice, to assess the biological importance of mammalian STI1.
Keywords: Molecular chaperones; Proteins -- Analysis; Heat shock proteins; Bioinformatics; Genetics -- Data processing